2017
DOI: 10.1093/bioinformatics/btx389
|View full text |Cite
|
Sign up to set email alerts
|

The interfacial character of antibody paratopes: analysis of antibody–antigen structures

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 31 publications
4
35
1
Order By: Relevance
“…Over the last decades, the increasing amount of antibody-antigen crystal structures has enabled the first quantitative insight into the physicochemical features of antibody-antigen interaction (Benjamin et al, 1984;Berzofsky, 1985;Burkovitz et al, 2013;Dalkas et al, 2014;Lawrence and Colman, 1993;MacCallum et al, 1996;Ofran et al, 2008;Peng et al, 2014;Raghunathan et al, 2012;Sela-Culang et al, 2013;Sivalingam and Shepherd, 2012). For example, it has been observed repeatedly that paratopes localize mostly, but not exclusively, to CDRs (Kunik et al, 2012a), and that certain amino acids are preferentially enriched or depleted in the antibody binding regions (Mian et al, 1991;Nguyen et al, 2017;Ramaraj et al, 2012;Sela-Culang et al, 2013;Wang et al, 2018). For epitopes, several analyses have shown that their amino-acid composition is essentially indistinguishable from that of other surfaceexposed non-epitope residues if the corresponding antibody is not taken into account (Kringelum et al, 2013;Kunik and Ofran, 2013;Ponomarenko and Bourne, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, the increasing amount of antibody-antigen crystal structures has enabled the first quantitative insight into the physicochemical features of antibody-antigen interaction (Benjamin et al, 1984;Berzofsky, 1985;Burkovitz et al, 2013;Dalkas et al, 2014;Lawrence and Colman, 1993;MacCallum et al, 1996;Ofran et al, 2008;Peng et al, 2014;Raghunathan et al, 2012;Sela-Culang et al, 2013;Sivalingam and Shepherd, 2012). For example, it has been observed repeatedly that paratopes localize mostly, but not exclusively, to CDRs (Kunik et al, 2012a), and that certain amino acids are preferentially enriched or depleted in the antibody binding regions (Mian et al, 1991;Nguyen et al, 2017;Ramaraj et al, 2012;Sela-Culang et al, 2013;Wang et al, 2018). For epitopes, several analyses have shown that their amino-acid composition is essentially indistinguishable from that of other surfaceexposed non-epitope residues if the corresponding antibody is not taken into account (Kringelum et al, 2013;Kunik and Ofran, 2013;Ponomarenko and Bourne, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies are key players as therapeutic agents because of their ability to bind the majority of targets and their suitability for protein engineering. [1][2][3][4] Description of the binding properties 5 and characterization of the paratope 6 is essential for understanding the function of the antibody. In the antigen-binding process, the most important region is the complementarity-determining region (CDR), which consists of six hypervariable loops that shape the paratope.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction force between molecules mainly depends on hydrophobic interactions, hydrogen bonds, and ionic bonds. The bond energy of hydrophobic interactions is approximately 1~2 kJ/mol, the hydrogen bond force is 1 to 2 times greater, and the ionic bond is the strongest, approximately one order of magnitude higher 29 . Through in-depth analysis of the interface residues, the local environment of the residues can be understood and improved by changing some of the amino acid sites.…”
Section: Resultsmentioning
confidence: 97%